Lessons from the stigma of COVID-19 survivors: A Marxist criticism appraisal - Lin, Jin-Long; Wang, Yu-Kun (Frontiers in Public Health, 2023)
Stigma refers to devalued stereotypes that create barriers for stigmatized individuals. During the COVID-19 pandemic, the stigmatization of survivors worsened existing inequalities and triggered mass hysteria. The paper delves into the stigmatization experienced by COVID-19 survivors and the role of Marxist criticism in analyzing this issue. The main findings from the empiricist tradition approach suggest that the perception of COVID-19 stigma is higher among those who are older, belong to ethnic minorities, lack social support, have manual occupations, and possess lower levels of education. The proposed destigmatization pathways include psychological counseling services, social support, and health education. Employing a Marxist perspective can aid in illuminating how economic practices and material conditions influence prevalent ideologies related to stigma. The stigmatization of COVID-19 survivors may be perceived as a consequence of social power inequality, although the current emphasis on individual characteristics as triggers for stigma may neglect the wider systemic forces in operation. Thus, it's crucial to establish improved social care policies to combat exploitation and oppression due to power imbalances. The ultimate objective of such an examination is to identify effective approaches to tackle and eradicate stigma regarding health-related concerns. An interdisciplinary approach integrating a pluralistic perspective would benefit investigating how social systems and individual attributes contribute to the exacerbation of social inequality and stigmatization.